Genetic polymorphism assessment in a new lentil (Lens culinaris Medik., 1787) collection using ISSR markers - Shamsiya E. Mammadova; Saltanat A. Aghayeva (Acta Biologica Sibirica, 2023)
ISSR markers were used in the study of the genetic diversity of 46 imported lentil varieties. The lentil collection had a strikingly high level of polymorphism (76%). The UBC 810 and UBC 809 primers have the highest polymorphism rates among the primers, exceeding 85.7%. The use of nine ISSR markers resulted in 69 pieces, with 76% displaying polymorphism. The computed average genetic diversity index ranged from 0.56 to 0.81, indicating a wide range of genetic variation among lentil genotypes. Accessions were classified into six unique groups as a consequence of cluster analysis. The most divergent genotypes within their respective clusters were identified as Flip 2010-96 and Flip 2011-41, Flip 2011-32 and Flip 2011-97, 10932 and Flip 2011-20, and Flip 2010-81 and Flip 2011-19. These findings bear noteworthy implications for the future of lentil breeding, cultivation, and protection. The observed genetic diversity imparts valuable insights that can be harnessed to fortify lentil crops, fostering resilience and adaptability. The identified distant genotypes present promising avenues for targeted breeding initiatives, facilitating the development of lentil varieties harboring diverse and desirable traits. In summation, this study contributes pivotal information to the scientific community, establishing a framework for subsequent research and progress in the improvement of lentil crops.